Kilka uwag o odpowiedzialności karnej kierownika podmiotu odpowiedzialnego albo jednostki organizacyjnej takiego podmiotu za naruszenie obowiązku złożenia wniosku o wszczęcie postępowania wyjaśniającego - Ochman, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article deals with a relatively new issue of the responsibility of the head of the responsible executive or an organisational unit of it for the breach of the obligation to submit a request for an inquiry. This issue became particularly interesting after the entry into force of the Act on Financial Liability of Public Officers for Gross Violations of Law, due to its introduction into the Polish legal system, a special legal regulation which is the basis for prosecution in this field. The author presents the relationship between the breach of the duty of an administrative obligation and criminal liability of persons obliged to submit a request for an inquiry into the rights of recourse in the case of payment of compensation by the State, unit of local government or other legal entity. The author analyses the problems indicated above, not only from the standpoint of the validity of the adoption of specific dogmatic solutions, but also in terms of their compliance with the rules of the criminal legislation.
Keywords: prawo karne; odpowiedzialność karna funkcjonariuszy publicznych